2022
DOI: 10.3389/fpubh.2022.1021495
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and work-related factors associated with burnout, resilience, and quality of life among healthcare workers during the COVID-19 pandemic: A cross sectional study from Malaysia

Abstract: IntroductionThe healthcare setting is a stressful and demanding work environment, and healthcare workers face a continuous expansion of their job roles and responsibilities. Past studies have shown that factors affecting burnout, resilience, and quality of life among healthcare workers merit further research, as there were inconsistent findings, especially with regards to the influence of demographic and work-related factors. Therefore, this study aims to determine whether demographic and work-related factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 66 publications
0
1
0
Order By: Relevance
“…Ang et al [ 17 ] suggested that resilience substantially correlates with age group, work grade, years of nursing experience, education level, and marital status. Marzo et al [ 18 ] found that income affects resilience. Furthermore, Oksuz et al [ 19 ] found a statistically significant relationship among resilience and age, gender, work experience, and working hours.…”
Section: Discussionmentioning
confidence: 99%
“…Ang et al [ 17 ] suggested that resilience substantially correlates with age group, work grade, years of nursing experience, education level, and marital status. Marzo et al [ 18 ] found that income affects resilience. Furthermore, Oksuz et al [ 19 ] found a statistically significant relationship among resilience and age, gender, work experience, and working hours.…”
Section: Discussionmentioning
confidence: 99%
“…This study further showed a statistically significant finding that the prevalence of COVID-19 infection was twice as much higher during the pre-vaccination period compared to that of the post-vaccination period (χ 2 = 41.446, p < 0.001). However, it is in contrast to other reports which showed a rise in the prevalence of SARS-CoV-2 infection among HCWs in the period following the introduction of COVID-19 vaccines compared to the prevaccination period attributed partly to the decrease in vaccine effectiveness to emerging variants of SARS-CoV-2 [17] Other attributable factors have to do with the significant increase in the incidence of COVID-19 around the world leading to issue of mental and psychological disturbances from long working hours resulting in lowered resilience, burnout, low quality of life (QoL) among HCWs, experiences of depressive and anxiety symptoms, with females, physicians, and less experienced Healthcare workers showing elevated levels of symptomology [18][19][20][21][22][23][24], The prevalence of COVID-19 infection among HCWs following the introduction of vaccines was low and comparable to a global estimate [25] This decline may be attributed to the success of the COVID-19 vaccination programme buttressing the effectiveness of the vaccine against infection with SAR-CoV-2 and probably combined with the improvement in the IPC measures adopted by HCWs across the state [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Previous findings suggest that demographic variables such as age, gender, educational qualifications, marital status, living residence, and professional background have been shown to influence resilience and the domains of quality of life among healthcare workers during the COVID-19 pandemic [ 29 31 ]. Therefore, the present study, aims to offer insights into the relationship between sociodemographic characteristics of Romanian physicians and their psychological resilience and quality of life.…”
Section: Introductionmentioning
confidence: 99%